2019
DOI: 10.1038/s41598-019-43483-1
|View full text |Cite
|
Sign up to set email alerts
|

Conserved, breed-dependent, and subline-dependent innate immune responses of Fayoumi and Leghorn chicken embryos to Newcastle disease virus infection

Abstract: Newcastle disease virus (NDV) is a threat to the global poultry industry, but particularly for smallholder farmers in low- and middle-income countries. Previous reports suggest that some breeds of chickens are less susceptible to NDV infection, however, the mechanisms contributing to this are unknown. We here examined the comparative transcriptional responses of innate immune genes to NDV infection in inbred sublines of the Fayoumi and Leghorn breeds known to differ in their relative susceptibility to infectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 36 publications
(36 reference statements)
0
10
0
Order By: Relevance
“…The combined analysis of three target tissues generated a more extensive understanding of response to infection with lentogenic NDV at the whole organism level. Other studies have compared differences between the expression of key immune genes in these genetic lines after an NDV challenge in embryo (Schilling et al, 2018;Schilling et al, 2019) and at 3 weeks of age under heat stress conditions (Saelao et al, 2018). Also, genetic markers of interest have been identified in a commercial line (Rowland et al, 2018;Saelao et al, 2019) and African ecotypes (Walugembe et al, 2019) after infection with this same lentogenic strain.…”
Section: Discussionmentioning
confidence: 99%
“…The combined analysis of three target tissues generated a more extensive understanding of response to infection with lentogenic NDV at the whole organism level. Other studies have compared differences between the expression of key immune genes in these genetic lines after an NDV challenge in embryo (Schilling et al, 2018;Schilling et al, 2019) and at 3 weeks of age under heat stress conditions (Saelao et al, 2018). Also, genetic markers of interest have been identified in a commercial line (Rowland et al, 2018;Saelao et al, 2019) and African ecotypes (Walugembe et al, 2019) after infection with this same lentogenic strain.…”
Section: Discussionmentioning
confidence: 99%
“…The Leghorn line Ghs6 was highly inbred from a cross of Leghorn lines; the Leghorn breed originated in Europe and provided the foundation stock for many commercial layer lines [ 28 , 29 , 30 ]. The Fayoumi line M15.2 was segregated from the Egyptian Fayoumi breed, has been highly inbred, and has large genetic distance from broiler and Leghorn lines [ 29 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…The Fayoumi line M15.2 was segregated from the Egyptian Fayoumi breed, has been highly inbred, and has large genetic distance from broiler and Leghorn lines [ 29 , 31 ]. From past comparisons between inbred Fayoumi and Leghorn chickens, the Fayoumi line has shown more resistance against various pathogens and stressful environments, suggesting superior immune responses [ 29 , 30 , 32 , 33 ]. In previous studies, Fayoumis have been demonstrated to have different expression of several HDPs [ 34 ] and association of genetic variants with disease response [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…We have previously described the use of the chick embryo, which becomes immunocompetent prior to hatch and in the protective environment of the shell, as a model to examine the innate immune response to NDV (Schilling et al, 2018, 2019). In one study, we found differential expression of innate immune genes from two highly inbred Fayoumi and Leghorn lines.…”
Section: Introductionmentioning
confidence: 99%